Increased Absolute Glutamate Concentrations and Glutamate-to-Creatine Ratios in Patients With Methamphetamine Use Disorders - Yang, Wenhan; Yang, Ru; Luo, Jing; He, Lei; Liu, Jun; Zhang, Jun (Frontiers in Psychiatry, 2018)
Abstract Introduction: Previous studies have indicated that changes in the concentration of glutamate and related metabolites may mediate the progression of addiction in patients with methamphetamine (MA) use disorders. In the present study, we utilized magnetic resonance spectroscopy (MRS) to investigate absolute glutamate concentrations and metabolite ratios in patients with MA addiction. We further analyzed the association between glutamate concentration and various clinical indicators. Methods: The present study included 29 unmedicated patients with clinically diagnosed MA dependence (mean age: 30.5±8.0 years) and 32 age-matched healthy controls (mean age: 32.9±8.2 years). Patients were evaluated using the Barratt Impulsiveness Scale (BIS-11). We also collected general information regarding the duration and dosage of drug use. Point-resolved spectroscopy was used to quantify the absolute concentrations of metabolites (glutamate, choline, N-acetylaspartate, glutamine, and creatine), as well as the ratio of glutamate to total creatine, using LCModel software. We then compared differences in glutamate levels and psychometric scores between the two groups. Results: Glutamate-to-creatine ratios in the pons were significantly higher in the MA group than in the control group (t=2.764, p=0.008). Glutamate concentrations in the pons were also significantly higher in the MA group than in the control group (t=2.390, p=0.020). However, no significant differences in the concentrations or ratios of other metabolites were observed between the two groups (all p>.05). Glutamate concentration was positively correlated with the duration of drug use (r=.401, p=.035) and the total dose of regular addiction (duration of addiction × regular addiction dose) (r=.207, p=.040), but not with BIS-11 scores. Conclusion: Our findings indicated that glutamate levels in the pons are significantly elevated in patients with MA use disorders, and that these levels are significantly associated with the duration and dose of drug use. Such findings suggest that glutamate concentration can be used as an objective biological marker for evaluating/monitoring disease status and treatment efficacy in patients with MA dependence.